Challenge-based education methodology within sustainable development environments: from ocean i3 to EmPACT i3 experience - Rekalde-Rodríguez, Itziar; Gil-Molina, Pilar; Cruz-Iglesias, Esther; Zinkunegi-Goitia, Olatz; Mendia-Urrutia, Aitor (Frontiers in Education, 2025)
This paper discusses the application of challenge-based education (CBE) in sustainability contexts, based on the Ocean i3 and EmPACT i3 projects. Within the framework of the Sustainable Development Goals (SDGs), especially SDG 3, CBE is proposed as a way to develop transversal and sustainability skills. The study describes its implementation in open, multicultural, multilingual, and cross-subject contexts, with the participation of regional agents. It highlights the creation of collaborative communities, redefining the role of the teacher as facilitator and the thoughtful use of log books. The experience shows how to structure active learning with local solutions, offering recommendations for universities seeking a transformational educational experience committed to sustainability.